Data integration of cost materials needs through a service oriented architecture (study case: pt x garment ungaran) - Christianto, Erwien; Utomo, Wiranto; Sulistyo, Wiwin (Journal of Advanced Computer Science & Technology, 2015)
Data processing is an important part of a garment company. With increasingly complex and developing a garment company, data processing and integration became a very important requirement. The need for data integration in determining the cost of materials becomes a very important part in the garment industry. Data distribution or dissemination from one to another section gives results in data duplication, so that it may cause the data to be inconsistent. In addition, the efficiency of the process in determining the cost of materials is highly needed to achieve the selling price determination target. Nowadays, there is web-based technology, which is capable of handle data integration service, called SOA (Service Oriented Architecture). Business processes (work flows) involving the supplier need to go back to the supplier with the output price that has been determined by the system, can be integrated with Web service with concentration of BPELSOA. By utilizing the SOA technology then data processing and integration problems that occurred in the garment industry could be made into an integrated information system, so that the problems in the garment industry can be solved.